Towards a Quantitative Model to Deal with Uncertainty Management in Software Projects - Barbosa, Jefferson Ferreira; de Moura, Hermano Perrelli; Marinho, Marcelo Luiz Monteiro (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2020.14614, 2020)
The evolution of thinking in project management has raised interest in areas not yet explored by researchers and practitioners of project management, including the management of uncertainties associated with risk management. The correct risk and uncertainty management in software projects can represent a competitive differential for the software development industry. Despite the increasing use of uncertainty management strategies, many projects still fail. Some recent studies show that the current techniques used to manage uncertainties organize the project's known information, but give little or no indication of the unknown information or uncertainties associated with the project. These techniques do not take into account the impact of existing dependency and interdependence relationships between the various sources of uncertainties in the project. This work will apply Action Research to develop a model with a focus on uncertainty quantification techniques. This work aims to present a model with a focus on uncertainty quantification techniques that take into account the relationships of dependencies and interdependence that exist between the sources of risks and uncertainties in software projects and as a result, contribute with the advance of state of the art in the practice of risk and uncertainty management in project software.